Vaccine Prophylaxis of Pneumococcal Infections in Children under Conditions of Severe Flood in the Amur River Basin - Chuchalin, Aleksandr G.; Onishchenko, Gennadiy G.; Kolosov, Victor P.; Kurganova, Olga P.; Zaitseva, Tatiana A.; Manakov, Leonid G.; Kholodok, Galina N.; Perelman, Juliy M.; Kozlov, Roman S.; Ivakhnishina, Natalia M.; Trotsenko, Olga E.; Bondarenko, Albina P. (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Background. Pneumococcal infection being one of the dominant causes of acute respiratory diseases and exacerbation of chronic ones is a serious problem for human health and society. The flood in the Amur river basin in the summer of 2013 created a special zone and risk conditions for the formation of respiratory pathology in the Far-Eastern region of Russia. We aimed to give clinical and epidemiological assessment of the effectiveness of vaccination programs of respiratory viral and pneumococcal infections and generalization of regional experience in the organization of a set of measures aimed at their prevention in the postflood period in the Far-Eastern region. Methods. The monitoring program includes children aged 2 to 5 years in the amount of 4988 with risk factors for pneumococcal infection. The pneumococcal conjugate vaccine Prevenar-13 was used for immunization. Data on the incidence of ARVI and pneumonia in children in pre- and postvaccination periods were to be recorded. The indicators and special criteria were used to assess the effectiveness of vaccination. To study the circulation of serovariants of pneumococcus in inflammatory diseases of the respiratory tract and nasopharyngeal carrier, bacteriological and molecular genetic methods (RT-PCR in the mode of multiprime detection) were used. Results. Differences in the frequency and range of serovariants of circulating isolates of pneumococcus in the postvaccinal period and in unvaccinated children, elimination of a number of serotypes, and appearance of circulation of nonvaccinated strains were revealed. The incidence of acute respiratory diseases and pneumonia among the vaccinated population for 2 years in the region decreased by 2.5 times. The coefficient of effectiveness of vaccination according to the indicator of morbidity of children with pneumonia reaches 75-100% with direct dependence on the age of children (r=0.98). Conclusion. Comparative statistical analysis revealed a high degree of effectiveness of regional programs with the methods of immunoprophylaxis of pneumococcal infections.